A Catalytic System for the Estragole to Anethole Isomerization Based on [RuCl(μ-Cl)(η6-p-cymene)2] - Menendez-Rodriguez, Lucia; Crochet, Pascale; Cadierno, Victorio (Current Green Chemistry, 2014)
An efficient, inexpensive and selective catalytic system for the industrially relevant isomerization of estragole to trans-anethole has been developed using the arene-ruthenium(II) dimer [RuCl(μ-Cl)(η6-p-cymene)2] in combination with P(OMe)3. As an example, using 100 mg of this complex and 38 μL of P(OMe)3 (1 equiv. per Ru), 10 mL of estragole could be quantitatively converted into anethole (98% trans-selectivity) after heating the mixture at 80ºC for 24 h. In addition, after separation of the anethole product by distillation, the catalytic system could be reused without loss of efficiency and selectivity.
Keywords: ruthenium